2004
DOI: 10.1088/0953-8984/16/23/024
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electrical transport properties of La0.67Ca0.33MnO3(LCMO):xZnO composites

Abstract: We have synthesized La0.67Ca0.33MnO3 (LCMO):xZnO () composites through a citrate gel route and have characterized them for magnetic and magnetotransport properties. In lower concentrations (), ZnO mostly goes into the perovskite lattice substituting Mn in LCMO and segregates less in the grain boundary region, but at higher concentration (x>0.13) it segregates mostly at the grain boundaries of LCMO and influences the transport properties significantly. A model is proposed which describes the overall resistivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 28 publications
0
35
1
Order By: Relevance
“…Also an increase in resistivity is observed due to the NiO doping of LSMO samples. As discussed in the literatures [26,27] there are two kinds of conduction channels, connected in parallel in the polycrystalline LSMO/xNiO composite samples. One is related to intragrain and the second is related to intergrain, hopping of the conduction electrons between the neighboring sites.…”
Section: Methodsmentioning
confidence: 99%
“…Also an increase in resistivity is observed due to the NiO doping of LSMO samples. As discussed in the literatures [26,27] there are two kinds of conduction channels, connected in parallel in the polycrystalline LSMO/xNiO composite samples. One is related to intragrain and the second is related to intergrain, hopping of the conduction electrons between the neighboring sites.…”
Section: Methodsmentioning
confidence: 99%
“…[ 5 , 6 ] Thus, many groups have attempted to improve the LFMR effect in manganite-based composites by incorporating a secondary phase, which not only creates additional artifi cial GBs but further increases the height of the tunneling barriers because of local structural disorder, chemical disorder, and spin disorder at the phase boundaries. [7][8][9][10][11][12][13] Various secondary phases including insulators, semiconductor oxides, and metals have been reported earlier but mostly in the form of randomly distributed granular bulk micro/nano-composites. [7][8][9][10][11][12][13] Recently, the magnetoresistance effect has been reported in several manganite composite thin fi lms, which could be more favorable for device applications.…”
Section: Introductionmentioning
confidence: 99%
“…The Curie temperature T C corresponding to the paramagnetic-ferromagnetic transition decreases slightly when the Mn excess is increased. This ~20 K decrease is very small when compared to the drastic drop usually observed in such composites as a result of interdiffusion between the manganite phase and the insulating phase [7][8][9] . This indicates that the composition of the manganite phase is almost constant throughout the series, as already observed by XRD.…”
mentioning
confidence: 67%
“…On the other hand, when long sintering times are used to reach proper densification, it is usually observed that the composition and properties of the manganite phase are drastically modified due to interdiffusion between the phases. [7][8][9] The present paper reports the synthesis and properties of a composite system that can be submitted to long sintering treatment without leading to significant modification of the manganite composition: these unique properties of the La 0.7 Ca 0.3 MnO 3 /Mn 3 O 4 system result from the fact that no compound with Mn/(La+Ca) > 1 exists in the composition, temperature and pressure ranges used during the synthesis of the composite samples. 10 An additional advantage of this system is the possibility to synthesize the composite samples in one step by thermal treatment of a spray-dried precursor, instead of mixing pre-synthesized manganite and insulating powders.…”
Section: Intrinsic Colossal Magnetoresistance (Cmr)mentioning
confidence: 99%